Centers of cultural enlightenment in the Touat region during the Ottoman era - Khedidji , Houari Boumediene; Lakehal , Cheikh (The Algerian Historical Journal, 2026)
The strategic location of Tuat region in the middle of the desert made it a meeting point and at the same time a gathering point for caravans trade crossing the desert, which gave its people the opportunity to interact and deal with merchants and practice trade, tis later was an important reason for the scientific and cultural movement of the region, the Tuat region was known for the spread of many scientific and cultural institutions, such as Mosques and Zawiyas, that embraced the scientific movement existing in the region and were credited with forming elites of eminent scholars. Through this study, we will attempt to cover the most important educational and cultural institutions that have made the region a cultural center that attracts students and scholars.